Enhancing China's Medium-Term Growth Prospects : The Path to a High-Income Economy - Nabar, Malhar; N'Diaye, Papa. (Washington, D.C. : International Monetary Fund, 2014)
China's current growth model- which has delivered steady and robust growth for two decades and lifted some 500 million individuals out of poverty-has become too reliant on credit and investment, and has begun to experience diminishing returns. Delays in advancing the government's reform agenda will mean that vulnerabilities continue to grow and the probability of stalled convergence increases. On the other hand, with reforms to accelerate TFP growth and shift the economy away from its continued reliance on capital accumulation, China can grow at a healthy pace and maintain its convergence toward the level of high income economies. Evidence from China's provinces indicates that there is room to improve productivity and sustain such a convergence toward the level of more prosperous economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet